Synchrotron energy-dispersive X-ray diffraction analysis of residual strains around friction welds between dissimilar aluminium and nickel alloys - Jun, T; Zhang, S; Golshan, M; Peel, M; Richards, D; Korsunsky, A (Trans Tech Publications, 2008)
Friction welding processes, such as friction stir welding (FSW) and inertia friction welding (IFW) are popular candidate procedures for joining engineering materials (including dissimilar pairs) for advanced applications. The advantages of friction welding include lack of large scale material melting, ability to join dissimilar materials, and relatively low propensity to introduce defects into the weld joint. For these reasons FSW and IFW have become the subjects of a number of studies aimed at optimising the joining operations to obtain improved joint strength and reduce distortion and residual stress. In the present study we used the diffraciton of high energy polychromatic synchrotron X-rays to measure interplanar lattice spacings and deduce nominal elastic strains in friction stir welds between dissimilar aluminium alloys AA5083 and AA6082, and in coupons from inertia friction welds between dissimilar nickel-base superalloys IN718 and RR1000. Energy-dispersive diffraction profiles were collected by two detectors mounted in the horizontal and vertical diffraction planes, providing information about lattice strains in two nearly perpendicular directions lying almost in the plane of the plate samples mounted perpendicularly to the incident beam. Two-dimensional maps of residual stresses in friction-welded joints were constructed. Apart from the 2D mapping techniques, the sin²ψ method (transmission) was also used in the case of inertia friction-welded joint between nickel alloys. Comparison between the two results allowed the variation of the lattice parameter with the distance from the bond line to be deduced. It was found that friction welding of two dissimilar materials with significant strength mismatch may lead to the creation of a region of compressive stress in the vicinity of the bond line, in contrast with the behaviour observed for joints between similar materials.